From nuclear transmutation to nuclear fission, 1932-1939 - Dahl, Per F. (Taylor & Francis, 2011)
From Nuclear Transmutation to Nuclear Fission, 1932-1939 deals with a particular phase in the early history of nuclear physics: the race among four laboratory teams to be the first to achieve the transmutation of atomic nuclei with artificially accelerated nuclear projectiles (protons) in high-voltage discharge tubes. This volume covers the background of the development of particle accelerators in the 1920s, the growth of the laboratories and their teams, the race itself, and its aftermath.